STAT3 is involved in IL-6-Mediated Downregulation of Hepatic Transporters in Mice - Walaa Ali Abualsunun; Micheline Piquette-Miller (Frontiers Media S.A., 2018)
Interleukin (IL)-6 decreases hepatic expression of numerous transporters. Although IL-6 signaling occurs through STAT3, the extent of the involvement of the STAT3 signaling pathway has not been elucidated. PURPOSE: Our objective was to investigate whether IL-6-mediated effects occur through STAT3, and whether PXR plays a role in this regulation. METHOD: PXR null (-/-) or wild-type (+/+) male mice were pre-dosed with a selective STAT3 inhibitor S3I-201 (7.5 mg/kg ip) or vehicle (n=5-8/group) 30 minutes before receiving a single dose of IL-6 (1 µg ip) or saline. Animals were sacrificed after 6 hours and liver samples were analyzed using qRT-PCR and western blotting. RESULTS: As compared to saline controls, IL-6 decreased the expression of Cyp3a, Abcb1a, Abcc3, and Slco1a4 20-70% similarly in PXR (+/+) and (-/-) mice at 6 hr, while downregulation of Abcb11, Abcc2, Slc10a1and Slco2b1 was only seen in PXR (+/+). Pre-administration of S3I-201 attenuated IL-6-mediated changes of most transporters in PXR (+/+) and PXR (-/-) mice. At early times after IL-6 administration (10-120 minutes), transcript levels of Socs3, PXR, Abcb1a, Abcc3, Abcb11, Slco1a4 and Slco2b1were increased in PXR (+/+) mice. CONCLUSIONS: Our findings demonstrate that IL-6 imposes a significant downregulation of numerous ABC and SLC transporters in liver primarily through activation of the STAT3 signaling pathway. Based on time-dependent changes in transporter expression, downregulation likely occurs downstream of STAT3 activation.  As IL-6 is elevated in many diseases, understanding the underlying mechanism(s) involved in transporter dysregulation will allow us to predict potential drug-disease interactions.